The use of structures of modification as a possible measure of language growth among students in San Francisco High School, Quezon City - Guimary, Portia Nena A. 1925- (1967)
This study examined the possibility of using structures of modification in English as a measure of language growth by determining the relationship between the amount of modification structures used and the increase in the year level. This study was observed in San Francisco High School, Quezon City.